Penyelesaian Sengketa Konsumen Antara Alvarendra Ataya Anas Dengan PT Citra Van Titipan Kilat (TIKI) (Analisa Putusan Mahkamah Agung No. 175K/Pdt.Sus-BPSK/2021) - Dedi Harianto; Aflah; Manullang, Ganesti Gebryella (Talenta Publisher, Universitas Sumatera Utara, 2023)
The implementation of goods delivery carried out by PT Citra Van Titipan Kilat (TIKI) as a provider of goods delivery services does not always run smoothly. As happened in BPSK Bekasi City Decision No. 011/REG/BPSK-BKS/2020, The formulation of the problems in this journal, namely how is the regulation of consumer dispute resolution in goods delivery service disputes in Indonesia, how is the responsibility of the goods delivery service business actor for consumer losses due to negligence that occurs in the goods delivery service business in Supreme Court Decision No. 175K/Pdt.Sus-BPSK/2021, and how is the analysis of considerations and judges' decisions related to the settlement of consumer disputes between Alvarendra Ataya Anas and PT Citra Van Titipan Kilat (TIKI) in Supreme Court Decision No. 175K/Pdt.Sus-BPSK/2021. The method used in writing this journal is the normative juridical method, namely library legal research, the nature of the research used is descriptive and analytical. The form of responsibility of PT Citra Van Titipan Kilat (TIKI) for consumer losses in BPSK Bekasi City Decision No. 011/REG/BPSK-BKS/2020 is in the form of administrative sanctions given to PT Citra Van Titipan Kilat (TIKI) in the amount of Rp1,000,000.00 (one million rupiah). BPSK Bekasi City Decision No. 011/REG/BPSK-BKS/2020 is in accordance with the applicable legal provisions.